PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, KOMPETENSI APARATUR DAN PERAN AUDIT INTERNAL TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERATING (Studi Empiris pada SKPD di Pemprov NTB) - M Ali Fikri Biana Adha Inapty; RR Sri Pancawati Martiningsih (Akuntabilitas, 2016)
This study aims to obtain empirical evidence about the effect of applying government accounting standards, competence human resources, and the role of internal audits of the quality of financial reporting information to the internal control system as moderating variable. the population in this study were all civil servants (PNS) in the regional work units (SKPD) Pemprov NTB. Sampling was done by purposive sampling of employees in the process of financial administration, an employee who makes the financial statements and the workers who are the subject of examination APIP of the Inspectorate. Analysis of the data used in this research is regression with moderating variables. the results of this study indicate that the government penewrapan government accounting standards, competency of personnel the role of internal audit had no significant effect on the quality of financial reporting information with the internal control system as moderating variableDOI: 10.15408/akt.v9i1.3583